Philosopher Kings and Tragic Heroes Essays on Images and Ideas from Western Greece - Reid, Heather L. (Heritage of Western Greece, 2016)
On at least one of Plato's visits to the sparkling city of Syracuse, he must have visited its famed theater and taken in a tragedy or two. He may also have reflected, as he sat there on the marble seats and looked up occasionally to glimpse the Ionian Sea, that his own adventure resembled that of a tragic hero. It had shining ideals, noble goals, great risk, a bit of hubris, and would end in death-nearly for the philosopher himself, and senselessly for his protégé, Dion. This connection between philosophy and drama goes back farther than Plato, though. It has roots in the plays of Syracuse's Epicharmus and can be seen in the earliest intellectual history of Magna Graecia, where such thinkers as Pythagoras, Xenophanes, and Empedocles blended philosophy, poetry, and performance. Sicily and Southern Italy, in particular, seem to have inspired the kind of original ideas that defy disciplinary designation. This collection of essays from a variety of disciplinary perspectives including archaeology, classics, philosophy, and art history, offers a refreshing new outlook on the Heritage of Western Greece.